Métodos de superação de dormência de sementes de Flamboyant - Bolognez, Claudinei Antonio (2012)
The Flamboyant (Delonix regia (Bojer ex Hook) Raf.) is an exotic ornamental species adapted to the conditions of the Brazilian territory, belonging to subfamily Caesalpinioideae and it has seeds with hard coat that promotes seed dormancy caused by the impermeability of seed coat to water and oxygen. The aim of this study was to test different types of mechanical scarification to overcome seedcoat dormancy of seed, associated with physical and biological aspects of Flamboyant. The study was conducted in laboratory and experimental area of the Department of Biological Sciences at the Institute of Exact and Natural Sciences, Federal University of Mato Grosso, in Rondonópolis, MT, from October 2011 to April 2012, the experimental field was protected by a screen shading retaining 50% of brightness. The treatments were: control, whose seeds had not been scarified, treatments with a hole in the coat, mechanical scarification with sandpaper number 150 for wood, water heated to 90 ° C with immersion of the seeds and water heating to 90 ° C and then immersion seeds leaving to cool to room temperature. Experimental design was completely randomized (CRD) with five treatments and four repetitions, totaling twenty installments of fifteen seeds each. With the observations, there were no significant differences between the means of overcoming the five methods employed in the work. To overcome dormancy in flamboyant the recommended method is immersion in water heated to 90 ° C and subsequent soaking of the seeds. The use of techniques to overcome flamboyant seeds may cause problems when growth in height and diameter of plants in the initial phase of establishment.